Caracterização da cama de peru visando gerenciamento e produção de biogás - Cé, Ana (2019)
Wastes from turkeys confinement production are presented as an alternative energy source. In this way, to evaluate the characterization and biochemical methane potencial (BMP) of turkey litter is shown as an important perspective for the energy reutilization and management of these wastes. The aim of this study was: i) to perform the physico and chemical characterization and BMP of turkey litter, ii) to obtain turkey litter indicators for the brazilian potential of methane generation e iii) to evaluate the different handling influence of the turkey litter with 50, 120 and above 400 days upon of birds housing. The methodology applied for physical and chemical characterization was according to APHA et al., (2012). The kinetic tests to evaluate the BMP of the three samples were conducted in batch, at mesophilic temperatures, according to VDI standard 4630 (2016). The highest volatile solids concentration obtained was to the surface layer (32.2%, m m-1). The indicators obtained from the turkey litter for the brazilian potential of methane generation were from 7.5 to 31 million m3 of CH4 with the wastes reutilization at different days of housing stemming from the turkey meat production from 2010 to 2017. The highest BMP value (289±14 LN CH4.kgSV add-1), VCH4N (35.1 m3 day-1) as well as energy electrical (71.3 kWh day-1) was found in the turkey litter of 50 housing days.